Sustained User Engagement in Health Information Technology: The Long Road from Implementation to System Optimization of Computerized Physician Order Entry and Clinical Decision Support Systems for Prescribing in Hospitals in England. (7th October 2016) - Cresswell, Kathrin M.; Lee, Lisa; Mozaffar, Hajar; Williams, Robin; Sheikh, Aziz; ,
Abstract : Objective: To explore and understand approaches to user engagement through investigating the range of ways in which health care workers and organizations accommodated the introduction of computerized physician order entry (CPOE) and computerized decision support (CDS) for hospital prescribing. Study Setting: Six hospitals in England, United Kingdom. Study Design: Qualitative case study. Data Collection: We undertook qualitative semi‐structured interviews, non‐participant observations of meetings and system use, and collected organizational documents over three time periods from six hospitals. Thematic analysis was initially undertaken within individual cases, followed by cross‐case comparisons. Findings: We conducted 173 interviews, conducted 24 observations, and collected 17 documents between 2011 and 2015. We found that perceived individual and safety benefits among different user groups tended to facilitate engagement in some, while other less engaged groups developed resistance and unsanctioned workarounds if systems were perceived to be inadequate. We identified both the opportunity and need for sustained engagement across user groups around system enhancement (e.g., through customizing software) and the development of user competencies and effective use. Conclusions: There is an urgent need to move away from an episodic view of engagement focused on the preimplementation phase, to more continuous holistic attempts to engage with and respond to end‐users.